Emotion and the Psychodynamics of the Cerebellum : a Neuro-Psychoanalytic Analysis and Synthesis. - Levin, Fred (Karnac Books, 2009)
This is a book about cognition, emotion, memory, and learning. Along the way it examines exactly how implicit memory ("knowing how") and explicit memory ("knowing that") are connected with each other via the cerebellum. Since emotion is also related to memory, and most likely, one of its organising features, many fields of human endeavour have attempted to clarify its fundamental nature, including its relationship to metaphor, problem-solving, learning, and many other variables. This is an attempt to pull together the various strands relating to emotions, so that clinicians and researchers ali.